2010
DOI: 10.1111/j.1744-7909.2010.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Mapping for Leaf Length and Leaf Width in Rice cv. IR64 Derived Lines

Abstract: The present study was conducted to identify quantitative trait loci (QTLs) for leaf size traits in IR64 introgression lines (INLs). For this purpose, selected F(2) populations derived from crosses between recurrent parent IR64 and its derived INLs, unique for leaf length and leaf width, were used to confirm QTLs. A total of eight QTLs, mapped on three chromosomes, were identified for the four leaf size traits in six F(2) populations. A QTL for leaf length, qLLnpt-1, in HKL69 was identified around simple sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…Alternatively, the regulation of qFLW4 may depend on factor(s) which are polymorphic between HB277 and D50. A similar location on chromosome 4 for a leaf width QTL has been detected in other genetic backgrounds (Ding et al 2011;Farooq et al 2010). The leaf width QTL present in this same interval in cv.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Alternatively, the regulation of qFLW4 may depend on factor(s) which are polymorphic between HB277 and D50. A similar location on chromosome 4 for a leaf width QTL has been detected in other genetic backgrounds (Ding et al 2011;Farooq et al 2010). The leaf width QTL present in this same interval in cv.…”
Section: Discussionmentioning
confidence: 52%
“…Further QTL were later identified on 10 of 12 rice chromosomes by analysing a set of recombinant inbred lines (RILs) and a BC 1 F 1 population bred from the same cross (Mei et al 2003(Mei et al , 2005. A similar QTL approach has been taken in other mapping populations (Ding et al 2011;Farooq et al 2010;Li et al 1998;Qian et al 2000;Wang et al 2011;Yue et al 2006), raising the number of relevant QTLs to over 100, distributed over all 12 rice chromosomes (http://www.gramene.org/). However, as yet none of these QTLs has been isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Marathi et al (2012) reported 19 novel QTLs and 15 QTL hotspots affecting plant architecture, including yield-related traits, using RILs developed from Pusa1266, a semi-dwarf, high-yielding cultivar. Further work identified several other QTLs regulating plant shape, including leaf length, leaf width, tiller number and panicle length (Farooq et al, 2010; Liu et al, 2010; Wang et al, 2010; 2011). Modifying plant architecture for architecture-based breeding will require identification of QTLs and their causal genes in different genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Among these QTLs, 1 QTL on chromosome 8 controlling length, width, and flag leaf area was at the same location. Since then, QTL mapping for flag leaf traits has been extensively conducted in different types of genetic populations, such as near isogenic lines, backcross inbred lines, doubled haploids (DHs), and F 2 , with more than 100 QTLs identified (Dong et al, 2003;Kobayashi et al, 2003;Shen et al, 2003;Wang et al, 2004;Yue et al, 2006;Cao et al, 2007;Tong et al, 2007;Farooq et al, 2010;Ding et al, 2011;Wang et al, 2011;Sonah et al, 2012;Chen et al, 2012). For example, Kobayashi et al (2003) mapped QTLs for FLL, FLW, and FLA using the Milyang23/Akihikari RIL population over 5 seasons, and found a total of 9 genomic regions involved in leaf development.…”
Section: Introductionmentioning
confidence: 99%